Production of reactive oxygen (H2O2) and nitrogen (NO) intermediates and TNF-α in mice genetically selected for high (H) and low (L) antibody response and experimentally infected with Leptospira serovar pomona - Haanwinckel, Maria Cristina Santos [UNESP]; Oliveira, Silvio Luis de [UNESP] (Sociedade Brasileira de Microbiologia, 2011)
The aim of the present study was to evaluate the activity of macrophages, and the production of TNF-α and antibodies against experimental infection by Leptospira serovar Pomona in mice genetically selected for High (H) or Low (L) humoral immune response. To evaluate macrophagic activity, peritoneal and splenic lavages were performed for determination of oxygen (H2O2) and nitrogen (NO) intermediates. The production of the tumor necrosis factor (TNF-α) was investigated through bioassays in serum and homogenates of splenic and hepatic cells of control and infected animals, as was as specific antibodies production. The immune response against serovar Pomona in those lines, was characterized by high antibody production, especially in later periods of the infectious process, whereas values of bacterial recovery in culture medium were lower. The production of reactives oxygen and nitrogen intermediate, also helped to eliminate Leptospira Pomona in both lines; H2O2 production an important factor in H IV-A, as well as NO production in L IV-A, especially in later post-inoculation periods. The same was detected for TNF-α. Results suggest that such lines could be an important model to investigate the pathogenesis and the immune response of animals against the several Leptospira serovars.
Keywords: Immunological aspects; Biozzi mice; Leptospira; Macrophages; Cytokines